Diversity Host Range and Community Analysis of Plant Parasitic Nematodes in Hill Area Ecosystems of Meghalaya - Firake, D. M.; Behere, G. T.; Kalita, L.; Thakur, N. S. Azad (Indian Journal of Hill Farming, 2016)
Diversity, host range and community analysis of major plant parasitic nematodes were studied in different crops at Umiam and adjoining areas in Meghalaya. Overall results revealed that about 13 genera belonging to 9 families of 2 orders of plant parasitic nematodes were found in Meghalaya. Amongst, Helicotylenchus, Rotylenchulus and Meloidogyne were predominant and have wide host range. The Spiral nematode, Helicotylenchus dihystera was the most frequently encountered species around the crop rhizosphere and ranked first in absolute density (172.60), relative density (67.61) and prominence value (344.94). The foliar nematode, Aphelenchoides spp. was observed in very few crops viz., tomato, cabbage, cauliflower, knol-khol, radish with 4% absolute frequency.